Eugenol-Preconditioned Mesenchymal Stem Cell-Derived Extracellular Vesicles Promote Antioxidant Capacity of Tendon Stem Cells In Vitro and In Vivo. (8th February 2022) - Li, Xiangze; Su, Zhan; Shen, Kaiying; Wang, Qi; Xu, Chencheng; Wang, Fuqiang; Zhang, Yuchi; Jiang, Dapeng
Abstract : Tendon stem cells (TSCs) are often exposed to oxidative stress at tendon injury sites, which impairs their physiological effect as well as therapeutic application. Recently, extracellular vesicles (EVs) derived from bone marrow mesenchymal stem cells (BMSCs) were shown to mediate cell protection and survival under stress conditions. The function of BMSC-EVs may be affected by pretreatment with various factors such as eugenol (EUG)—a powerful antioxidant. In our previous study, we found that H2 O2 significantly impaired TSC proliferation and tenogenic differentiation capabilities. Apoptosis and intracellular ROS accumulation in TSCs were induced by H2 O2 . However, such H2 O2 -induced damage was prevented by treatment with EUG-BMSC-EVs. Furthermore, EUG-BMSC-EVs activated the Nrf2/HO-1 pathway to counteract H2 O2 -induced damage in TSCs. In a rat patellar tendon injury model, the ROS level was significantly higher than that in the normal tendon and TSCs not pretreated showed a poor therapeutic effect. However, EUG-BMSC-EV-pretreated TSCs significantly improved tenogenesis and matrix regeneration during tendon healing. Additionally, the EUG-BMSC-EV group had a significantly improved fiber arrangement. Overall, EUG-BMSC-EVs protected TSCs against oxidative stress and enhanced their functions in tendon injury. These findings provide a basis for potential clinical use of EUG-BMSC-EVs as a new therapeutic vehicle to facilitate TSC therapies for tendon regeneration.